Antibiotic use patterns and factors associated with leukocyte decrease in COVID-19 patients with suspected secondary infections: A cross-sectional study in Indonesia - Ginting, Pricella A.; Padmasawitri, Tjokorde IA.; Hanum, Nadia; Nurhayati, Raden D.; Soeroto, Arto Y.; Amalia, Lia (Narra Sains Indonesia, 2025)
Antibiotics are frequently prescribed to coronavirus disease 2019 (COVID-19) patients, often without evidence of bacterial superinfection, increasing the risk of antibiotic resistance and posing a public health threat. The aim of this study was to evaluate antibiotic prescribing patterns in COVID-19 patients with suspected secondary infections and to assess the association between antibiotic use and clinical outcomes, particularly leukocyte count. The study analyzed 376 hospitalized COVID-19 patients from two hospitals in Bandung, Indonesia, between 2020 and 2022. All included patients were aged ≥17 years with confirmed COVID-19, leukocyte count >11,000 μg/L, and received antibiotic therapy. The Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) and drug utilization (DU) 90% were used to assess prescribing patterns. The patients’ demographic characteristics, clinical and culture results were also collected. Our data indicated that most patients received multiple antibiotics (>2), with prescribing patterns significantly associated with age, confirmed bacterial pathogen, length of hospital stay and having tuberculosis infection. The most frequently identified pathogens included Gram-positive bacteria Staphylococcus aureus, Staphylococcus haemolyticus and Gram-negative bacteria Klebsiella pneumoniae, Acinetobacter baumannii, and Escherichia coli. The most frequently prescribed antibiotics were azithromycin, levofloxacin, and ceftriaxone. No significant association was found between the number of antibiotics prescribed and clinical outcome (leukocyte normalization). Broad-spectrum antibiotics from the World Health Organization (WHO) AWaRe